Alpha Female Representation as Ideal Women in Henry Manampiring’s The Alpha Girls Guide - Haekal Muhammad; Hapsari Dwiningtyas, S.Sos, MA (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2017)
This research started from the hardship that women experience. Currently women are still being discriminated and face obstacles for life in a lot of sectors. One of the solution provided comes from Henry Manampiring who introduced the concept of Alpha Female in his book named The Alpha Girls Guide: Menjadi Cewek Smart, Independen, dan Anti-Galau. This research aimed to understand how Alpha Female Representation written in Henry Manampiring’s book work as a form of empowerment to women. Analysis done using Roland Barthes’ semiotic models and Naomi Wolf’s Power Feminism Theory. The analysis is targeted to the chapters in Alpha Girls’ Guide The research concludes that most of this book support women to be empowered by providing women with choices, supporting women in career and education sector, defending woman to be respected, and inviting wmen to inspire other woman to move forward. However, in certain parts Manampiring is still trapped in patriarchal concept that still chained women and failed to defend women’s choice that has differences with the concept that he suggest. The example is the ban on woman to initiate relationship first, the impression that shown woman as the only responsible actor in nurturing and educating children, and push to woman to beautify themselves even if its only done for their own self and not for others. More than that, Manampiring tends to use masculine language that may be hard to accept for some woman. Ultimately, Alpha Female representation as an ideal women lead to empowerment that still has some issues and can’t be applied to all women.